2023
DOI: 10.23960/jhptt.12323-30
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of twisted disease and cultivation practice of shallot farmers in Bantul coastal area, Yogyakarta, Indonesia

Abstract: Shallot (Allium cepa var. aggregatum L.) is an important commodity in horticulture and Indonesian foods. In Bantul Regency, Yogyakarta, Indonesia, shallot twisted diseases caused by Fusarium spp. significantly reduced yield quality and quantity. Supportive condition for plant-pathogen interaction needed for twisted disease development. This research aimed to measure the twisted disease incidence and observe the cultivation practice applied by shallot farmers in the Bantul coastal area as environmental aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Fusarium attack shallots during the rainy season, leading to twisted disease (Wibowo et al, 2023). The pathogen, Fusarium spp., is a soil-borne pathogen characterized by purplish-white, slightly orange-white, cream, or white-like cotton colonies.…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium attack shallots during the rainy season, leading to twisted disease (Wibowo et al, 2023). The pathogen, Fusarium spp., is a soil-borne pathogen characterized by purplish-white, slightly orange-white, cream, or white-like cotton colonies.…”
Section: Introductionmentioning
confidence: 99%
“…The Fusarium wilt disease caused by Fusarium oxysporum is a foremost threat to shallot production. In particular, percent incidence and yield losses due to the Fusarium wilt disease in shallot crops increase with a predicted continuing trend (Wibowo et al, 2023). The Fusarium wilt can reduce bulb yield by up to 50% (Hadiwiyono et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Mariani et al [6]'s research disclosed that all shallots in West Nusa Tenggara were affected by moler disease, with an average incidence rate of 64.71%, primarily caused by Nectria haematococca [6]. Meanwhile, Wibowo et al [7] observed shallot farming practices in the Bantul coastal area, noting that during the rainy season, Samiran sub-village had the highest disease incidence at 33.97%, whereas during the dry season, Depok sub-village experienced a 20.14% incidence rate. Sono sub-village exhibited the lowest disease rates, at 12.44% and 0% during the rainy and dry seasons, respectively.…”
Section: Introductionmentioning
confidence: 99%